The Emergent Properties of an Ethical Leadership When Aligned with the Systems Engineering Handbook and Code of Ethics. Issue 3 (6th October 2021) - Fraga, Anabel
ABSTRACT: It is not easy to define leadership and the characteristics a leader must have. Some authors prefer one or another skill, but definitions are diverse. Some sources try to indicate what it means and its implications. A holistic ethical leadership model cannot be defined circularly, but it must be understood, such as a praxis. Leadership means more than its common definition; it means truth, ethics, empathy, and much more. In this case, it is of importance the definition of leadership, and in particular the ethical leadership. Also, the role of the leader is important, their education, their skills, and their influence. The need for ethical leadership in systems engineering is essential to be highlighted. The Code of Ethics of INCOSE and the Handbook do not merge the concept of leadership and ethics. That is why it is vital to show the need for alignment among both documents in terms of ethical leadership. Also, an explicit reference to this concept is needed in both documents because leadership needs to be honest, and ethics is a role to provide it. In this paper, we analyze the definitions found in the current INCOSE Code of Ethics and INCOSE Handbook regarding ethical leadership, its implications, and its application is explained and aligned to the ethical systems engineering idea. Also, examples of ethical behavior will be introduced to explain emergent properties. It will exemplify that applying ethical leadership will work in favor of the development of successful systems.